Therapeutic Efficiency of Proteins Secreted by Glial Progenitor Cells in a Rat Model of Traumatic Brain Injury - Salikhova, Diana I.; Golovicheva, Victoria V.; Fatkhudinov, Timur Kh; Shevtsova, Yulia A.; Soboleva, Anna G.; Goryunov, Kirill V.; Dyakonov, Alexander S.; Mokroysova, Victoria O.; Mingaleva, Natalia S.; Shedenkova, Margarita O.; Makhnach, Oleg V.; Kutsev, Sergey I.; et al. (International journal of molecular sciences, 2023)
Traumatic brain injuries account for 30–50% of all physical traumas and are the most common pathological diseases of the brain. Mechanical damage of brain tissue leads to the disruption of the blood–brain barrier and the massive death of neuronal, glial, and endothelial cells. These events trigger a neuroinflammatory response and neurodegenerative processes locally and in distant parts of the brain and promote cognitive impairment. Effective instruments to restore neural tissue in traumatic brain injury are lacking. Glial cells are the main auxiliary cells of the nervous system, supporting homeostasis and ensuring the protection of neurons through contact and paracrine mechanisms. The glial cells’ secretome may be considered as a means to support the regeneration of nervous tissue. Consequently, this study focused on the therapeutic efficiency of composite proteins with a molecular weight of 5–100 kDa secreted by glial progenitor cells in a rat model of traumatic brain injury. The characterization of proteins below 100 kDa secreted by glial progenitor cells was evaluated by proteomic analysis. Therapeutic effects were assessed by neurological outcomes, measurement of the damage volume by MRI, and an evaluation of the neurodegenerative, apoptotic, and inflammation markers in different areas of the brain. Intranasal infusions of the composite protein product facilitated the functional recovery of the experimental animals by decreasing the inflammation and apoptotic processes, preventing neurodegenerative processes by reducing the amounts of phosphorylated Tau isoforms Ser396 and Thr205. Consistently, our findings support the further consideration of glial secretomes for clinical use in TBI, notably in such aspects as dose-dependent effects and standardization.